Nocturnal Enuresis and its Homoeopathic Management (Homoeopathy for All, 2023)
In the absence of congenital urinary  tract malformations or congenital  or acquired central nervous system  problems, nocturnal enuresis is defined  as intermittent incontinence during  sleep in a child aged 5 years or older.  [1] Enuresis is generally distressing  for both children and parents, and it  has a negative impact on family life  in many circumstances. Self-esteem  issues, social isolation, low academic  achievement, and psychological issues  are all common.[1]
Keywords: congenital; psychological